2021
DOI: 10.1021/acsami.1c13551
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Self-Assembled Magnetic Micropaddles at Liquid Surfaces

Abstract: Cooperative controls of magnetic microswimmers are desired for complex micromanipulation and microassembly tasks. Self-assembled magnetic micropaddles as microswimmers that can locomote freely and cooperate at liquid surfaces are proposed inspired by the paddling motion. The micropaddles are self-assembled with metallic disks under a rotating magnetic field, and they are endowed with controlled propulsion in the precessing field. The micropaddles can locomote freely with a maximum speed of approximately 3.3 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Micromanipulation Based on Micropartners. Manipulating some cargoes floating at liquid surfaces by pushing or pulling them has been achieved in our previous work using different microrobots, 26,33 where these delivered cargoes cannot escape from the microrobots due to the sufficient capillary attractions. The connected microdisks here can also manipulate microparts in similar ways.…”
Section: Locomotion Characteristics Of the Micropartnersmentioning
confidence: 99%
See 1 more Smart Citation
“…Micromanipulation Based on Micropartners. Manipulating some cargoes floating at liquid surfaces by pushing or pulling them has been achieved in our previous work using different microrobots, 26,33 where these delivered cargoes cannot escape from the microrobots due to the sufficient capillary attractions. The connected microdisks here can also manipulate microparts in similar ways.…”
Section: Locomotion Characteristics Of the Micropartnersmentioning
confidence: 99%
“…In contrast, interfacial robots actuated by external stimuli, such as light, ,, electrostatic fields, and magnetic fields, can have their dimensions down to several micrometers for various micromanipulations. In particular, the magnetically powered microrobots have recently aroused attraction due to their appropriate biological compatibilities and excellent mobolity in enclosed spaces, where efficient actuation and control strategies are the key challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Another class of magnetic micromotors can be operated at the liquid-air interface for environmental remediation and micromanipulation, 40,41 and the cooperative or interactive behaviours of multiple magnetic micromotors have also been studied. Two decades ago, Grzybowski et al 42 reported the dynamic interaction of millimetre-sized magnetized disks at the liquid-air interface, in which system the dynamic equilibrium was dominated by hydrodynamic force and magnetic force owing to the magnetic potential produced by a permanent magnet.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the electrical conductivity of Na 3 V 2 (PO 4 ) 2 F 3 , researchers have adopted several effective methods, such as carbon coating, [ 13,14 ] heterogeneous ions doping, [ 15–19 ] and particle nanocrystallization. [ 20 ] Moreover, different preparation methods, including high‐temperature solid‐state method, [ 21 ] sol‐gel method, [ 18 ] solvothermal method, [ 22–24 ] and electrostatic spinning method [ 25,26 ] have been used for the synthesis of Na 3 V 2 (PO 4 ) 2 F 3 . However, none of these methods are effective in obtaining pure phase, which greatly limited its practical application.…”
Section: Introductionmentioning
confidence: 99%